2012
DOI: 10.1007/s00134-012-2580-6
|View full text |Cite
|
Sign up to set email alerts
|

International comparison of the performance of the paediatric index of mortality (PIM) 2 score in two national data sets

Abstract: The PIM2 score was valid in the FS population. The recalibration based on GB data could be applied to FS PICUs. Such recalibration may facilitate comparisons between countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The mortality rate of our study cohort was 4.3%, which is comparable (3.4%–7.4%) with that of other recent PICU/NICU studies . CNS complications were the most common sequelae, which is also consistent with a previous study .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mortality rate of our study cohort was 4.3%, which is comparable (3.4%–7.4%) with that of other recent PICU/NICU studies . CNS complications were the most common sequelae, which is also consistent with a previous study .…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have reported that the PIM2 is a good tool for predicting the mortality and poor outcomes of critically ill children . In this study, we confirmed the value of the PIM2 score in evaluating the outcomes of patients admitted to a PICU/NICU.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…PELOD-2 was developed and validated with a dataset that originated from only two countries (France and Belgium) which are different from other parts of the world population. [ 27 28 ] Thus, the extrapolation to other countries has to be verified. Interobserver variability was not studied and should be evaluated in future studies on new populations.…”
Section: Prognostic Scoresmentioning
confidence: 99%
“…PIM2 was found to have excellent discriminatory power, good calibration and therefore to be a potentially useful tool in the assessment of quality of care in Japanese PICUs. Likewise, Leteurtre et al [67] sought to compare the performance of PIM2 in 14 French and 1 Belgian PICUs. The authors undertook a recalibration of the score in both the French-Belgian (FB) and Great Britain and Ireland (GBI) data sets.…”
Section: Paediatricmentioning
confidence: 99%